The magic of believing - Bristol, Claude M. (Claude Myron), 1891-1951. (New York : Pocket Books, 1948)
" This inspirational masterpiece reveals how faith and belief are the keys to success - as a special bonus it includes the author's classic on unlocking the prospering powers of your mind, TNT: It Rocks the Earth. As if by magic, some people know how to make wishes come true. In this classic exploration of mental visualization and autosuggestion, journalist and businessman Claude M. Bristol discloses the secret of turning belief into success. Bristol learned early in life that if he clearly visualized his goals, and strongly believed in them, he would attain them. Since its first appearance in 1948, The Magic of Believing has persuaded millions of the literal truth of the Biblical text: "If thou canst believe, all things are possible to him that believeth." This volume also includes Bristol's first book, TNT: It Rocks the Earth (1932), a concise guide to harnessing your mental dynamite"--
"This inspirational masterpiece reveals how faith and belief are the magic keys to success - and as a special bonus includes the author's classic on unlocking the prospering powers of your mind, T.N.T.: It Rocks the Earth"--
Keywords: Telepathy; Self-actualization (Psychology); Success; SELF-HELP / Personal Growth / Success; SELF-HELP / Personal Growth / General